Collateral damage for ingroup members having outgroup friends: Effects of normative versus counternormative interactions with an outgroup. (July 2017) - Eller, Anja; Gomez, Angel; Vázquez, Alexandra; Fernández, Saulo
When people are aware that an ingroup member has an outgroup friend, they tend to improve their intergroup attitudes, which is known as the extended contact hypothesis . Thus far, no research has tested how the perceived degree of normativity of the intergroup interaction affects the evaluation of the ingroup member through which extended contact is experienced. Results of three studies showed that when contact was normative (i.e., positive contact with a liked outgroup, or negative contact with a disliked outgroup), the ingroup member was evaluated positively, while when the contact was counternormative (i.e., negative contact with a liked outgroup or positive contact with a disliked outgroup) the ingroup member was evaluated negatively. This effect was mediated by perceived threat posed by the ingroup member who experiences the intergroup contact and perceived similarity of the participant with the ingroup member (Experiments 2–3). In summary, the perceived normativity of the extended contact affects the perception of the ingroup member who experiences the contact, turning him/her into a "white" or a "black" sheep in the eyes of the ingroup.